An exploration of volunteers supporting patients with dementia and cognitive impairment on acute hospital wards: a qualitative study - Charalambous, Pauline Elizabeth (2019)
Background: Volunteers are widely used in hospital NHS Trusts but little is known about the service provided for the support of patients with dementia on acute hospital wards.